THE MULTIMODALITY SEMIOTIC ANALYSIS : OPPRESSION OF MENSTRUATING WOMEN IN VIERRATALE'S YOUTUBE MUSIC VIDEO “DATANG BULAN” - Ramadaniar, Putri; Sukmono, Ilham; Reza Akbar, Muhamad; Kuswanti, Ana (Universitas Jabal Ghafur, 2024)
In the era of pop culture, women are closely related to oppression in all areas of life by Patriarchal thinking. The menstrual condition experienced by women becomes a weapon of oppression to be able to limit and marginalize women in society. This condition is realized in Vierratale's YouTube music video entitled